2017
DOI: 10.1371/journal.pone.0184922
|View full text |Cite|
|
Sign up to set email alerts
|

Modulating lysosomal function through lysosome membrane permeabilization or autophagy suppression restores sensitivity to cisplatin in refractory non-small-cell lung cancer cells

Abstract: Lung cancer is the leading cause of cancer-related deaths. Most patients develop resistance to platinum within several months of treatment. We investigated whether triggering lysosomal membrane permeabilization (LMP) or suppressing autophagy can restore cisplatin susceptibility in lung cancer with acquired chemoresistance. Cisplatin IC50 in A549Pt (parental) and A549cisR (cisplatin resistant) cells was 13 μM and 47 μM, respectively. Following cisplatin exposure, A549cisR cells failed to elicit an apoptotic res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 61 publications
2
54
0
1
Order By: Relevance
“…Following experiments further demonstrated that LC3B‐II/LC3B‐I ratio was strikingly increased and p62 level was remarkably reduced in DDP resistant NSCLC cells compared with their parental counterparts. In other words, autophagic activity was enhanced in DDP resistant NSCLC cells, which is in agreement with prior studies (Ren et al, ; Circu et al, ). However, Sirichanchuen et al () demonstrated that LC3 protein expression and autophagosome numbers were reduced in DDP resistant H460 cells than that in parental H460.…”
Section: Discussionsupporting
confidence: 93%
“…Following experiments further demonstrated that LC3B‐II/LC3B‐I ratio was strikingly increased and p62 level was remarkably reduced in DDP resistant NSCLC cells compared with their parental counterparts. In other words, autophagic activity was enhanced in DDP resistant NSCLC cells, which is in agreement with prior studies (Ren et al, ; Circu et al, ). However, Sirichanchuen et al () demonstrated that LC3 protein expression and autophagosome numbers were reduced in DDP resistant H460 cells than that in parental H460.…”
Section: Discussionsupporting
confidence: 93%
“…From the available literature, it is obvious that the mechanism conferring chemoresistance to CDDP is complex, highly multifactorial and often specific for distinct types of cells 5,[17][18][19][27][28][29] . In the present study, we performed a comparative analysis of proteomic signatures of UKF- Despite this phenomenon has not yet been described for CDDP-chemoresistance in Nbl, it is a generally accepted mechanism for other types of cancers [32][33][34] . Similarly, to those studies, we found that UKF-NB-4 CDDP cells acquire a specific phenotype resulting in a pronounced lysosomal enrichment and up-regulation of V-ATPases that are required for proper lysosomal acidification to allow efficient sequestration of drugs, including CDDP 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that chloroquine and hydroxychloroquine accumulate in lysosomes (lyso somotropism) and inhibit their function. In vitro, chloro quine can destabilize lysosomal membranes and promote the release of lysosomal enzymes inside cells 76 . Although evidence of this latter mechanism is scarce, the ability of these drugs to interfere with lysosomal activity has been repeatedly documented [77][78][79] .…”
Section: Molecular Effects Inhibition Of Lysosomal Activity and Autopmentioning
confidence: 99%